Biodiversity and technological-functional potential of lactic acid bacteria isolated from spontaneously fermented chia sourdough - Dentice Maidana, Stefania; Aristimuño Ficoseco, Cecilia; Bassi, Daniela; Cocconcelli, Pier Sandro; Puglisi, Edoardo; Savoy, Graciela; Vignolo, Graciela Margarita; Fontana, Cecilia Alejandra (Elsevier, 2019)
Chia, is a gluten-free, rich in proteins, oilseed that is “on trend” as an alternative ingredient in food production, adding nutritional value. As a reservoir of natural biodiversity, lactic acid bacteria development, during spontaneous chia flour fermentation (sourdough) for 10 days, were investigated by culturing and high throughput sequencing (HTS). Culture-dependent analysis showed a rapid increase in total LAB numbers from the second day of sourdough refreshment. Taxonomical identification of LAB isolates by rep-PCR and further 16S rRNA sequencing was performed. Besides Among identified LAB by culture-dependent approach, species from genus Enterococcus were the most abundant; Lactococcus (Lc. lactis), Lactobacillus (L. rhamnosus) and Weissella (W. cibaria) species were also isolated. By HTS, twelve OTUs belonging to LAB genera were identified during chia sourdough fermentation with an increased Lactobacillus diversity. Enterococcus (E.) faecium, E. mundtii, W. cibaria and L. rhamnosus were detected as dominant species in the final propagation stages while Bacillus and Clostridium were mostly present during first fermentation stages. The investigation of biotechnological and safety traits (acidification ability, protein hydrolysis, exopolysaccharides production, antimicrobial activity and antibiotic resistance) of 15 representative LAB strains was performed. Strains characterization led to the selection of Lc. lactis CH179, L. rhamnosus CH34 and W. cibaria CH28 as candidates to be used as novel functional starter culture for gluten-free chia fermented products. As far as we know, this is the first study providing information on the molecular inventory of LAB population during spontaneous fermentation of chia sourdough.